Language from the body : iconicity and metaphor in American Sign Language - Taub, Sarah F., 1968- (Cambridge University Press, 2001)
What is the role of meaning in linguistic theory? Generative linguists have severely limited the influence of meaning, claiming that language is not affected by other cognitive processes and that semantics does not influence linguistic form. Conversely, cognitivist and functionalist linguists believe that meaning pervades and motivates all levels of linguistic structure. This dispute can now be resolved conclusively by evidence from signed languages. Signed languages are full of iconic linguistic items: words, inflections, and even syntactic constructions with structural similarities between their physical form and their referents' form. Iconic items can have concrete meanings and also abstract meanings through conceptual metaphors. Language from the Body rebuts the generativist linguistic theories which separate form and meaning and asserts that iconicity can only be described in a cognitivist framework where meaning can influence form.